1989
DOI: 10.4141/cjas89-083
|View full text |Cite
|
Sign up to set email alerts
|

Rate and Efficiency of Gain, From Weaning to Slaughter, of Steers Given Hay, Hay Supplemented With Rumtnal Undegradable Protein, or Concentrate

Abstract: Holstein steers were given milk from birth until they reached a weight of 100 kg.Beginning at 60 kg, they received gradually increasing amounts of one of three different diets and these became their sole diet after milk was withdrawn. The three diets were: (a) 85% grass hay and 15% concentrate (group 1); @) the same diet with enough rumen undegradible protein (formaldehyde-treated canola meal) added to raise the crude protein content by l0 g kg-r (group 2); arrd (c) 85% concentrate and l5Va grass hay (group 3)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0
2

Year Published

1990
1990
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 30 publications
1
2
0
2
Order By: Relevance
“…The higher levels of performance achieved as concentrate input was increased were attributed to higher efficiency of utilization of ME for growth resulting from the lower proportion of energy derived from digestible cell walls. While the present study and that of Thomas et al (1988) have involved comparisons of high-silage and high-concentrate diets, Bailey (1989) obtained similar improvements in efficiency of energy use when the proportion of concentrates in diets based on dried forage was increased from 15 to 85% of total DM intake. However, in contrast to the results of these studies, Baker et al (1982) found that the performance of young, growing cattle remained constant when diets with silage concentrate ratios of 100:0, 50:50 and 10:90 were offered at equal energy intakes.…”
Section: Discussionsupporting
confidence: 77%
“…The higher levels of performance achieved as concentrate input was increased were attributed to higher efficiency of utilization of ME for growth resulting from the lower proportion of energy derived from digestible cell walls. While the present study and that of Thomas et al (1988) have involved comparisons of high-silage and high-concentrate diets, Bailey (1989) obtained similar improvements in efficiency of energy use when the proportion of concentrates in diets based on dried forage was increased from 15 to 85% of total DM intake. However, in contrast to the results of these studies, Baker et al (1982) found that the performance of young, growing cattle remained constant when diets with silage concentrate ratios of 100:0, 50:50 and 10:90 were offered at equal energy intakes.…”
Section: Discussionsupporting
confidence: 77%
“…Sampling in our study may have ceased too early to detect differences among treatments. Other researchers have observed either transient increases (Teleni et al, 1989) or no difference (Bailey, 1989) in insulin concentrations from the feeding of protein sources with a higher potential for ruminal escape.…”
Section: Discussionmentioning
confidence: 96%
“…Lactating dairy cattle abomasally infused with casein had reduced plasma NEFA concentrations compared with noninfused controls (Istasse et al, 1986). However, growing lambs infused with casein (Barry et al, 1982) or growing cattle fed high-escape sources of protein (Bailey, 1989) showed no differences in NEFA concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…또한, Ponnampalam 등 (2003)은 사료 중에 조단백질의 증가는 도체의 지방함량을 감소시 킨다고 하였으며, Berge 등(1993)은 거세우에 조단백질의 급여증 가는 근육의 생산량을 증가시키고, 연도의 감소를 보고하였다. Leng (1985)은 조단백질을 다량 급여하면 사료섭취량이 증가하고, 장내 아미노산 흡수율의 증가로 증체량이 향상된다고 하였다 (Bailey, 1989). 따라서, 본 연구는 비육단계별 농후사료의 조단백 질 수준 차이가 한우 거세우의 도체 특성 및 육질에 미치는 영향 을 구명하여, 농가 생산성 향상 및 소득증대에 기여하고자 실시하 였다.…”
unclassified